EFEKTIVITAS TERAPI QIGONG TERHADAP FUNGSI KOGNITIF LANSIA DI PANTI SOSIAL TRESNA WERDHA KHUSNUL KHOTIMAH PEKANBARU - Yuni Elita Sari; Ari Pristiana Dewi; Safri " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Changes of cognitive function including the deterioration in tasks that require speed and tasks that require short-term memory. This will effect the friction of elderly’s role in social interaction in the community and family. The research aim to determine the the effectiveness of Qigong therapy on cognitive function of elderly. This research used quasy experiment design with non-equivalent control group. This research was conducted in Panti Sosial Tresna Werdha Khusnul Khotimah Pekanbaru with 34 samples, which devided into 17 as experimental group and 17 as control group and choosen by purposive and random sampling technique. Experimental group was given Qigong therapy for 20 minutes 2 times a week for 4 weeks (8 sessions), meanwhile control group were not. The cognitive function was measured with Mini Mental State Examination (MMSE). The analysis used univariat by using frequencies and bivariat by using Dependent Sample T Test and Independent Sample T Test. The result of this research showed that increasing mean of MMSE score in experiment group with 2.82 and incresing mean of MMSE score 0.29. Statistic analyze showed that was significant increasing cognitive fuction after giving intervention of experiment group with p value 0.000 (<0.05). The conclusion is Qigong Therapy effect on cognitive function of elderly and recommended to be applied for nursing intervention to help optimize cognitive function of elderly.  Keywords: Cognitive function, MMSE, Qigong